Comparison of Encryption Algorithms for Multimedia (Rajshahi University Journal of Science and Engineering, 2016)
Cryptographic techniques play crucial role when users exchange information. Multimedia plays an important role in learning and sharing experiences. When multimedia contents are shared among the users, it faces security threats. Usually multimedia contents takes much space. Encryption technique should be time efficient. In this work we consider four encryption techniques: Blowfish, AES, XOR and RSA and four types of media content: text, image, audio and video. Simulation shows that AES is time efficient than others. Comparing between symmetric and asymmetric cryptography, symmetric cryptographic techniques take less time than asymmetric technique.